Left atrial appendage closure in end-stage renal disease and hemodialysis: data from a German multicenter registry - Fink, Thomas; Paitazoglou, Christina; Bergmann, Martin W.; Sano, Makoto; Keelani, Ahmad; Sciacca, Vanessa; Saad, Mohammed; Eitel, Charlotte; Heeger, Christian-Hendrik; Skurk, Carsten; Landmesser, Ulf; Thiele, Holger; et al. (Catheterization and cardiovascular interventions, 2023)
Background Left atrial appendage closure (LAAC) has emerged as an alternative to oral anticoagulation (OAC) for stroke prevention in patients with atrial fibrillation (AF). OAC treatment has been proven feasible in mild-to-moderate chronic kidney disease (CKD). In contrast, the optimal antithrombotic management of AF patients with end-stage renal disease (ESRD) is unknown and LAAC has not been proven in these patients in prospective randomized clinical trials. Objectives The objective of this study is to evaluate safety and efficacy of LAAC in patients with ESRD. Methods Patients undergoing LAAC were collected in a German multicenter real-world observational registry. A composite endpoint consisting of the occurrence of ischemic stroke/transient ischemic attack, systemic embolism, and/or major clinical bleeding was assessed. Patients with ESRD were compared with propensity score-matched patients without severe CKD. ESRD was defined as a glomerular filtration rate < 15 ml/min/1.73 m2 or chronic hemodialysis treatment. Results A total of 604 patients were analyzed, including 57 with ESRD and 57 propensity-matched patients. Overall, 596 endocardial and 8 epicardial LAAC procedures were performed. Frequency of major complications was 7.0% (42/604 patients) in the overall cohort, 8.8% (5/57 patients) in patients with ESRD, and 10.5% (6/57 patients) in matched controls (p = 0.75). The estimated event-free survival of the combined endpoint after 500 days was 90.7 ± 4.5% in patients with ESRD and 90.2 ± 5.5% in matched controls (p = 0.33). Conclusions LAAC had comparable procedural safety and clinical efficacy in patients with ESRD and patients without severe CKD.